Identifikasi Variabel Penelitian, Jenis Sumber Data dalam Penelitian Pendidikan - Nurul Melani Haifa; Indah Nabilla; Virda Rahmatika; Rully Hidayatullah; Harmonedi Harmonedi (Lembaga Pengembangan Kinerja Dosen, 2025)
In educational research, identifying variables and determining data sources are essential components in designing a systematic and accurate study. Research variables refer to the elements that are observed and measured within a study. These variables can include student achievement, motivation, teaching strategies, or learning environment conditions. Generally, variables are categorized as independent, dependent, control, or moderator variables. The independent variable is the influencing factor, while the dependent variable is the outcome. Control variables are held constant to avoid interference, and moderator variables affect the strength or direction of the relationship. The process of identifying variables begins with formulating the research problem and objectives. By reviewing theoretical frameworks and previous studies, researchers can focus their investigation on measurable aspects. For instance, in a study about the effectiveness of online learning on student performance, the independent variable is online learning, while the dependent variable is student achievement. Beyond identifying variables, researchers must also determine the appropriate types of data sources. Data sources are generally divided into two categories: primary and secondary. Primary data are collected directly from research subjects, such as through interviews, observations, or questionnaires. Secondary data, on the other hand, are obtained from existing sources like documents, books, journals, or official reports. The choice of data source must align with the research approach—quantitative, qualitative, or mixed methods. In quantitative research, primary data such as test scores or survey responses are used to measure variables numerically. In qualitative research, in-depth interviews and observations are commonly used to explore meanings and context. Using both types of data in combination can enhance data validity through triangulation. Ultimately, researchers must ensure the validity and reliability of their data, while also maintaining ethical standards in data collection and reporting. By understanding how to identify variables and select appropriate data sources, educational research can yield credible findings that contribute meaningfully to educational theory and practice.